Pengelolaan Dana Bantuan Operasional Sekolah Pada MTsN Se Kota Padang - Melviani Melviani; Anisah Anisah; Rifma Rifma; Yulianto Santoso (Journal of Educational Administration and Leadership, 2022)
The results of this study aimed to find out information related management and school operational assistance at MTsN in Padang City is 48 people, so the number of samples is 35 respondents. Data collection was carried out using a questionnaire that had been tested for validity and reality. The average formula is used to process research data.. random sampling technique. The data shows that the response of managers regarding the management of school operational aid funds in mastering the procedures for managing boss funds is in the good category with an average score of 4.02, the use of school operational assistance funds is in a good category with an average value of 4.33. following steps: Verify returned questionnaire data and check for correctness and completeness, if any are incomplete, try to complete it., Perform data tabulation and score respondents' answers. Giving a score for each item with the following details: very good was given a score of 5, good was given a score of 4, quite good was given a score of 3, less well was given a score of 2, and not good was given a score of 1., Describes the data that has been processed into a table. It can be concluded that manager's response to City is at a moderate level with a score of 4.17.